Smith-Lemli-Opitz Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
Two sibs, a male aged 3 years and female aged 7 months, with a variant of Smith-Lemli-Opitz (SLO) syndrome and atypical sterol metabolism are reported from the Kennedy Krieger Institute, Johns Hopkins University, Baltimore, MD.